Perbandingan Pemberian ASI Dengan Susu Formula Terhadap Kejadian Ikterus Pada Bayi Hiperbilirubin Fisiologis Di Ruang NICU BLUD RS Konawe - La Ode Liaumin Azim; Sitti Hermin; Darmin; Mustafa; Nirwana; Fauzan Azhari Marzuki; Feni Fenedsia Ridson (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat (LPPM), Institut Teknologi Dan Kesehatan (ITK) Avicenna, 2022)
Background: Jaundice is a condition where the baby's body looks yellow caused by hyperbilirubin. Hyperbilirubin often occurs in the first few days after birth. This condition if not treated immediately will result in stunted growth of toddlers. Objective: This study aims to determine the ratio of breastfeeding and formula milk to the incidence of jaundice in infants with physiological hyperbilirubinemia in the NICU BLUD Konawe Hospital. Methods: This type of research is a comparative descriptive study. The population of this study were all mothers and infants with physiological hyperbilirubinemia who were treated at the NICU BLUD Konawe Hospital from July to August 2022 totaling 56 people, and the samples for this study were mothers and their babies who experienced physiological hyperbilirubinemia and met the inclusion criteria. Results: Research results showed eating habits (p=0.000) exclusive breastfeeding (p=0.000). Conclusion: There is a significant difference in the degree of jaundice between babies who are breastfed and those who are fed formula. This difference is indicated by the jaundice degree of infants who receive breast milk are lower than infants who receive formula milk